Recycling of Organic Waste: An Overview of Pálinka Distillery Mash Composting - Borges Silva, Lara Rúbia; Kardos, Levente (Journal of Central European Green Innovation, 2022)
Organic waste generation has been extending to an alarming level in most areas of the world, and its sustainable management is required. In Hungary, the amount of organic waste is increasing significantly, especially in pálinka manufacturing - a Hungarian hard liquor - producing a great quantity of mash residue, mostly grape pomace spent wash, a non-hazardous food waste that is a suspension left over by the distillation of fermented spirits. Around two hundred thousand tons of fruit waste are generated annually, and its full recycling and legal disposal are unprecedented in Hungarian distilling plants, threatening the environment if disposed of incorrectly. In this paper, we focused on reviewing the Pálinka mash composting, where the biggest challenge for its treatment is its initial pH, around 4, which can be successfully neutralized with mineral additives. The applied additives were chosen by their beneficial physical, chemical, and biological qualities. Accordingly, andesite and alginite were employed in the experimental composting. The results of our observation have confirmed that the mineral additives can establish valuable compost or fertilizer, favourably altering the dynamics of the decomposition and synthesis reactions. As an experiment on mash composting technology, we also tested the mature mash compost in culture vessel experiments for heavy metal adsorption capacity of the ma tube mash compost using lettuce (Lactuca sativa) and tomato (Solanum Lycopersicum) as test plants. The plants were irrigated with lead (Pb), and iron (Fe) contaminated water, and then it was determined the metals accumulation capacity of the plants and growing media with an Atomic Absorption Spectrometer (AAS). The study could compare the rate of heavy metal accumulation by different plant parts and ratios of Pálinka mash compost in the growing media.